2017
DOI: 10.1111/gcb.13753
|View full text |Cite
|
Sign up to set email alerts
|

Widespread production of nonmicrobial greenhouse gases in soils

Abstract: Carbon dioxide (CO ), methane (CH ), and nitrous oxide (N O) are the three most important greenhouse gases (GHGs), and all show large uncertainties in their atmospheric budgets. Soils of natural and managed ecosystems play an extremely important role in modulating their atmospheric abundance. Mechanisms underlying the exchange of these GHGs at the soil-atmosphere interface are often assumed to be exclusively microbe-mediated (M-GHGs). We argue that it is a widespread phenomenon for soil systems to produce GHGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 100 publications
(197 reference statements)
1
52
0
Order By: Relevance
“…This includes mechanisms that are not driven by methanogenic archaea (e.g., Liu et al, 2015) or those that are governed by alternative pathways and nonoxygen sensitive enzymes (Tang et al, 2016), such as CH 4 production in freshwater lakes as a by-product of phosphorus metabolism rather than C or energy metabolism (Yao et al, 2016) or CH 4 production in oxygenated shallow marine waters by zooplankton (Schmale et al, 2017). There have been other recent indications of nonmicrobial CH 4 production, although only at very small levels insignificant in the context of the global CH 4 budget (Table 1) (Wang, Lerdau, & He, 2017). The presence of CH 4 in oxic zones in lakes is likely driven by the transport of dissolved CH 4 from CH 4 production areas, rather than aerobic, algae-related CH 4 production (Encinas Fernández et al, 2016).…”
Section: 1002/2017rg000559mentioning
confidence: 99%
“…This includes mechanisms that are not driven by methanogenic archaea (e.g., Liu et al, 2015) or those that are governed by alternative pathways and nonoxygen sensitive enzymes (Tang et al, 2016), such as CH 4 production in freshwater lakes as a by-product of phosphorus metabolism rather than C or energy metabolism (Yao et al, 2016) or CH 4 production in oxygenated shallow marine waters by zooplankton (Schmale et al, 2017). There have been other recent indications of nonmicrobial CH 4 production, although only at very small levels insignificant in the context of the global CH 4 budget (Table 1) (Wang, Lerdau, & He, 2017). The presence of CH 4 in oxic zones in lakes is likely driven by the transport of dissolved CH 4 from CH 4 production areas, rather than aerobic, algae-related CH 4 production (Encinas Fernández et al, 2016).…”
Section: 1002/2017rg000559mentioning
confidence: 99%
“…Vigano et al, 2008;Fraser et al, 2015;Rey, 2015;Wang et al, 2017), which are more important in arid and semiarid environments. Vigano et al, 2008;Fraser et al, 2015;Rey, 2015;Wang et al, 2017), which are more important in arid and semiarid environments.…”
Section: Reflections By Ka Smith T Ball F Conen Ke Dobbie and mentioning
confidence: 99%
“…, Wang et al. ), Lee et al. () found that thermal emission of CO 2 and CH 4 from dried green leaves of four species, as well as cellulosic filter paper and basswood wood, increased exponentially from 25°C to 55°C.…”
Section: Introductionmentioning
confidence: 98%
“…These emissions are typically very low at temperatures below 30°C, but increase exponentially at higher temperatures, particularly above %50°C (but well below the ignition point of organic matter). While this process is not well characterized (reviewed by Carmichael et al 2014, Wang et al 2017, Lee et al (2012) found that thermal emission of CO 2 and CH 4 from dried green leaves of four species, as well as cellulosic filter paper and basswood wood, increased exponentially from 25°C to 55°C. Rates varied appreciably among plant materials implying that chemical composition is a potential factor in emission rates.…”
Section: Introductionmentioning
confidence: 99%